Characteristics of a high-power ion beam deflection system necessary to deflect the hypothetical asteroid 2017 PDC. Issue 1 (March 2018) - Brophy, John; Strange, Nathan; Goebela, Dan; Johnson, Shawn; Mazanek, Dan; Reeves, David
Abstract: The July 2027 impact date for the hypothetical asteroid 2017 PDC, that is the subject of an emergency response exercise, leaves just over ten years to implement a deflection approach. The analyses herein allocate four years to the design, fabrication, assembly, test and launch of a notional high-power Ion Beam Deflection (IBD) vehicle to meet a launch readiness date no later than May 2021. Using this launch date along with estimates for the vehicle mass and performance characteristics of the electric propulsion system, low-thrust trajectory analyses indicate a 2.56-year flight time to rendezvous with 2017 PDC. This would leave 3.6 years to execute the actual deflection phase. A 160-kW IBD vehicle could deflect 2017 PDC by at least one Earth radius within this time provided the asteroid's actual diameter was less than about 140 m and its density was 2 g/cm 3 or less. Larger diameters and/or higher densities would require a higher power IBD vehicle, multiple IBD vehicles, or a longer deflection phase. Ion beam deflection is largely independent of the characteristics of the threat object, but its effectiveness, like all deflection approaches, is sensitive to both the asteroid mass and the time available for deflection. The characteristics of IBD, i.e., large standoff distance between the spacecraft and the asteroid surface, as well as ion beam divergence angles of a few degrees, facilitate the possible simultaneous use of multiple IBD vehicles to improve the performance and robustness of the asteroid deflection. The 65-cm diameter, 20-kW NEXIS ion thruster developed in support of the Jupiter Icy Moons Orbiter mission concept is particularly well suited for application to a high-power IBD system. It has demonstrated a small ion beam divergence angle and operation at 20 kW for over 2000 h. Completion of the development and flight qualification of this technology would significantly reduce the risk and time necessary to respond to the discovery of potentially hazardous asteroid in the size range of 50- to 140-m diameter.